Task Types Found in the Textbooks “Bahasa Inggris: When English Rings A Bell” and Bright an English Course for Junior High School - Nurul Huda; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2020)
This research is a descriptive research that is aimed to describe the task types and to see the frequent task types that appeared in the textbooks entitled “Bahasa  Inggris: When English Rings a Bell” and Bright an English Course for junior high school.  The data was gained by using a data format. The data format is a table to classify the types the task types found in the textbooks. The data format is adapted from Nunan’s typology of task (1999). The result of this research revealed that most of the task types proposed by Nunan (1999) were covered by these two textbooks. However, some of the tasks had the highest frequency in each textbooks, while some had the least. In addition, there were some subcategories that were ignored in each textbooks